Tafsir simbolik pada tradisi megengan: analisis semiologi di Desa Trucuk, Bojonegoro - Putri Meida Kusumahati; Arief Sudrajat Arief Sudrajat (Departemen Pendidikan Sosiologi FISHIPOL UNY, 2024)
The Megengan tradition is a ritual carried out before the month of Ramadan as a form of gratitude for being given by Allah SWT. This research examines the meaning of symbols found in the Megengan Tradition in Trucuk Village, Bojonegoro Regency. The theory used in this research is Roland Barthes' Semiotic Theory. Research finds that the Megengan Tradition is full of symbolic meanings that reflect the spiritual, social and cultural values ​​of the local community. Through processions such as ater-ater, tahlilan, tumpeng rice, and urap-urap, people express gratitude, togetherness, and spiritual discipline. Tumpeng rice, for example, symbolizes spiritual achievement and a harmonious relationship with God, while the various side dishes depict blessings and abundance of good fortune. The semiotic approach in this research succeeded in identifying and understanding the deeper meaning of this tradition, showing that the Megengan Tradition functions as spiritual preparation for Ramadan and strengthens the social and cultural ties of Trucuk Village residents, enriching the local cultural heritage